1985
DOI: 10.1126/science.230.4722.170
|View full text |Cite
|
Sign up to set email alerts
|

Halite Particles Injected into the Stratosphere by the 1982 El Chichón Eruption

Abstract: Halite particles about 2 micrometers in size were collected by a quartz crystal microbalance cascade impactor from the El Chichón eruption cloud in the lower stratosphere during April and May 1982. These particles are probably derived from the erupted chloride-rich, alkalic magma. Enrichments of hydrogen chloride and increases in optical depolarization in the eruption cloud observed by lidar measurements may reflect the influence of the halite particles. There is evidence that the halite particles reacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 12 publications
2
65
0
Order By: Relevance
“…These circumstances are consistent with the observational results concerning the increase in the amount of aerosol particles in the Antarctic atmosphere in 1983 (Hofmann and Rosen, 1985;Ito et al, 1986). Halite particles which would have been formed by the condensation of vapors from a salt dome under El Chichon were detected in the stratosphere (23*N, 111*W) with about 7% of the total mass on May 1982 (Woods et al, 1985). The modified sea-salt (or halite) particles collected in the Antarctic upper troposphere are considered to be derived from the eruption of El Chichon.…”
Section: Data and Methods Of Trajectory Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…These circumstances are consistent with the observational results concerning the increase in the amount of aerosol particles in the Antarctic atmosphere in 1983 (Hofmann and Rosen, 1985;Ito et al, 1986). Halite particles which would have been formed by the condensation of vapors from a salt dome under El Chichon were detected in the stratosphere (23*N, 111*W) with about 7% of the total mass on May 1982 (Woods et al, 1985). The modified sea-salt (or halite) particles collected in the Antarctic upper troposphere are considered to be derived from the eruption of El Chichon.…”
Section: Data and Methods Of Trajectory Analysissupporting
confidence: 91%
“…The spectrum resembles that of sea-salt particles with the exception of the presence of Si and absence of Cl. It is conceivable that the particle B was originally sea-salt or halite and subsequently be modified through chemical reactions with acidic material in the atmosphere (e.g., Martens et al, 1973;Okada et al, 1978;Woods et al, 1985). On the basis of the results of the morphological examination and X-ray analysis applied to 66 particles of 0.1-1.6*m radius, the number frequencies for the four types of particles are summarized in Table 1.…”
Section: Data and Methods Of Trajectory Analysismentioning
confidence: 99%
“…[30] Indeed, although the reactions occurring between gases/aerosols and silicate ash particles in volcanic plumes remain poorly understood, it has been observed that halogens (HF and HCl), alter ashes, producing significant amounts of halide salts at the surface of ashes, in particular halite (NaCl) [Stoiber and Rose, 1974;Woods et al, 1985]. As a general rule, halite is one of the predominant species released on the first exposure of volcanic ash to water [Delmelle et al, 2007;Witham et al, 2005].…”
Section: A Possible Additional Time Marker: the 1991 Volcán Hudson Ermentioning
confidence: 99%
“…They have also been generated in the troposphere in unusual situations such as the oil well burning in Kuwait (e.g. see Lowenthal et al, 1993), and in the stratosphere by the eruption of alkaline volcanoes such as El Chichon (Woods et al, 1985). There are clear indications that chlorine chemistry, and to a greater (and somewhat surprising) extent bromine chemistry, goes on at high latitudes at polar sunrise (Jobson et al, 1994).…”
Section: Introductionmentioning
confidence: 96%